Lipid lowering activity of novel N-(benzoylphenyl)pyridine-3-carboxamide derivatives in Triton WR-1339-induced hyperlipidemic rats. (4th November 2016) - Abu Farha, Rana; Bustanji, Yasser; Al-Hiari, Yusuf; Al-Qirim, Tariq; Abu Shiekha, Ghassan; Albashiti, Rabab
Abstract: Context : Dyslipidemia is a major risk factor for the development of cardiovascular diseases. Many dyslipidemic patients do not achieve their target lipid levels with the currently available medications, and most of them may experience many side effects. Objective : The present work aimed toward identifying a new class of novel nicotinic acid-carboxamide derivatives as promising antihyperlipidemic compounds. Materials and methods : Six novel N -(benzoylphenyl)pyridine-3-carboxamide derivatives were synthesized using acid chloride pathways. All structures were confirmed using 1 H-NMR, 13 C-NMR, IR, and HRMS. The evaluation of biological activity was conducted using Triton WR-1339-induced hyperlipidemic rats model. Results : This study revealed that some of the newly synthesized novel N -(benzoylphenyl)pyridine-3-carboxamide derivatives mainlyC4 andC6 possessed significant antihyperlipidemic activities on lipid components TG and TC ( p value <0.05). Discussion and conclusion : This research opens the door for new potential antihyperlipidemic compounds derived from nicotinic acid that need further optimization of their biological activities.